2022
DOI: 10.7759/cureus.29928
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Risk of Non-alcoholic Fatty Liver Disease in Women With Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a complex hormonal disorder associated with complications throughout various body organs. Previous studies have shown evidence of liver disease in some women with PCOS. In this study, we attempted to explore the risk of non-alcoholic fatty liver disease (NAFLD) in PCOS women and the specific factors involved in its development. We searched PubMed, PubMed Central, Medline, and ScienceDirect for articles related to the topic, screened those articles according to our inclusion/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…This association was further affirmed by Harsha et al, who identified a 38.3% prevalence rate of NAHSD among women with polycystic ovaries, linking it to elevated levels of cholesterol, insulin, and liver enzymes, with hyperandrogenism identified as a significant predictor (12)(13)(14)(15). Sarkar et al also reinforced the connection between PCOS and NAHSD, advocating for routine screening for hepatic steatosis in patients diagnosed with PCOS (16)(17)(18). In our cohort, 46.5% of the women with PCOS were diagnosed with hepatic steatosis, indicating a substantial overlap between these two conditions.…”
Section: Discussionmentioning
confidence: 91%
“…This association was further affirmed by Harsha et al, who identified a 38.3% prevalence rate of NAHSD among women with polycystic ovaries, linking it to elevated levels of cholesterol, insulin, and liver enzymes, with hyperandrogenism identified as a significant predictor (12)(13)(14)(15). Sarkar et al also reinforced the connection between PCOS and NAHSD, advocating for routine screening for hepatic steatosis in patients diagnosed with PCOS (16)(17)(18). In our cohort, 46.5% of the women with PCOS were diagnosed with hepatic steatosis, indicating a substantial overlap between these two conditions.…”
Section: Discussionmentioning
confidence: 91%
“…В исследованиях, в которых использовался многофакторный анализ, было отмечено, что сывороточные андрогены являются независимыми предикторами развития НАЖБП у этой категории пациенток [43]. Несмотря на значимость таких факторов риска, как ожирение и инсулинорезистентность, в развитии НАЖБП гиперандрогения, по-видимому, является наиболее существенным фактором у пациенток с СПКЯ [44]. Согласно метаанализу [45] у пациенток в пременопаузе с СПКЯ риск развития НАЖБП повышается в 2,5 раза.…”
Section: влияние женских половых гормонов на риск развития и прогресс...unclassified
“…Although the association between NAFLD and PCOS has been widely studied in adults, liver manifestations in adolescents with PCOS are largely unaddressed in the current literature. There are only seven original studies examining hepatic steatosis exclusively in adolescent patients [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Hepatic fibrosis has been assessed only in one study of PCOS patients, which included an adolescent sample [ 24 ].…”
Section: Introductionmentioning
confidence: 99%